Phase I Trial of MCARH109, a G Protein-Coupled Receptor Class C Group 5 Member D (GPRC5D)-Targeted Chimeric Antigen Receptor T-Cell Therapy for Multiple Myeloma: An Updated Analysis - Jurgens, Eric M; Firestone, Ross S; Chaudhari, Jagrutiben; Hosszu, Kinga; Devlin, Sean M; Shah, Urvi A; Landa, Jonathan; McAvoy, Devin P; Lesokhin, Alexander M; Korde, Neha; Hassoun, Hani; Tan, Carlyn R; et al. (Journal of clinical oncology, 2025)
MCARH109 is a first-in-class G protein-coupled receptor, class C, group 5, member D (GPRC5D)-targeted chimeric antigen receptor (CAR) T-cell therapy for patients with relapsed/refractory multiple myeloma. This phase I clinical trial included 17 patients and determined that MCARH109 is safe at a maximum tolerated dose of 150 × 10 CAR T cells. In this updated analysis, no new serious adverse events were reported at a median follow-up of 37 months. Overall, 12 (71%) of 17 patients responded, including seven (70%) of 10 patients previously treated with B-cell maturation antigen-targeted therapy. The median duration of response was 8.6 months (95% CI, 5.7 to not reached [NR]) with two patients sustaining a stringent complete response at the time of last follow-up, 32 months and 41 months, respectively. The median overall survival (OS) was NR and the 3-year OS estimate was 59% (95% CI, 40 to 88). Possible GPRC5D loss via immunohistochemistry was observed in 6 (60%) of 10 patients at relapse. High-dimensional spectral cytometry-based immune profiling associated an activated T-cell phenotype at apheresis with a response to MCARH109.